The cast [compact disc, unabridged] : a novel - Steel, Danielle (Recorded Books, LLC, 2018)
When Kait Whittier teams up with producer Zack Winter to launch a television series, she finds a second family among the cast and crew, but in the midst of it all Kait is forced to confront the greatest challenge a mother can ever know.